ANALISIS DAMPAK PEMBANGUNAN INFRASTRUKTUR JALAN TERHADAP KONDISI SOSIAL DAN EKONOMI MASYARAKAT DI JALAN IRIGASI - Siti Nurhaliysa Halim; Mariani Sonda; Spedy Paereng (Jurnal Ekonomi dan Bisnis, 2024)
This research aims to determine the impact of road infrastructure development on the social and economic conditions of communities on irrigation roads. The data collection techniques used to obtain data in this research were observation and questionnaires. Data analysis in this study used the Wilcoxin sign-rank test analysis. From the results of the analysis that has been carried out, the research results show that the development of road infrastructure has a positive and significant effect on education and health income.